Robust Clustering of Open Access Journal Based on Scopus Journal Metrics Database - Rizki Agung Wibowo; Khoirin Nisa; Amril Samosir (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan)
Background: Open-access is free online access to articles, journal, conferences proceedings, book series and trade journal which provides unrestricted and permit the users to read, download, print, copy and link to the articles. Many articles that discuss the journal metrics using basic statistical methods to discribe the journal.